React 16 essentials : a fast-paced, hands-on guide to designing and building scalable and maintainable web apps with React 16 /: a fast-paced, hands-on guide to designing and building scalable and maintainable web apps with React 16. (2017) - Fedosejev, Artemij; Boduch, Adam
No abstract available